Influence of Patch Factors and Connectivity on the Avifauna of Fragmented Polylepis Forest in the Ecuadorian Andes. (22nd June 2013) - Tinoco, Boris A.; Astudillo, Pedro X.; Latta, Steven C.; Strubbe, Diederik; Graham, Catherine H.
Abstract: Human‐induced alteration of habitat is a major threat to biodiversity worldwide, especially in areas of high biological diversity and endemism. Polylepis (Rosaceae) forest, a unique forest habitat in the high Andes of South America, presently occurs as small and isolated patches in grassland dominated landscapes. We examine how the avian community is likely influenced by patch characteristics ( i.e ., area, plant species composition) and connectivity in a landscape composed of patches of Polylepis forest surrounded by páramo grasslands in Cajas National Park in the Andes of southern Ecuador. We used generalized linear mixed models and an information‐theoretic approach to identify the most important variables probably influencing birds inhabiting 26 forest patches. Our results indicated that species richness was associated with area of a patch and floristic composition, particularly the presence of Gynoxys (Asteraceae). However, connectivity of patches probably influenced the abundance of forest and generalists species. Elsewhere, it has been proposed that effective management plans for birds using Polylepis should promote the conservation of mature Polylepis patches. Our results not only suggest this but also show that there are additional factors, such as the presence of Gynoxys plants, which will probably play a role in conservation of birds. More generally, these findings show that while easily measured attributes of the patch and landscape may provide some insights into what influences patch use by birds, knowledge of other factors, such as plant species composition, is essential for better understanding the distribution of birds in fragmented landscapes.